Case-control study on intestinal intussusception: implications for anti-rotavirus vaccination - Vincenzo Restivo; Claudio Costantino; Gabriele Giorgianni; Mario Cuccia; Fabio Tramuto; Giovanni Corsello; Alessandra Casuccio; Francesco Vitale (Taylor & Francis Group, 2018)
Background: Intussusception represents the most common cause of abdominal emergency among young children but nearly 75% of cases are still considered idiopathic. Research design and methods: A case-control study was conducted among Sicilian children aged 0-59 months with a hospital admission for intussusception between 2009 and 2015 to identify factors associated with intussusception onset. Results: Overall, 125 cases and 190 controls were recruited for the study. Birth order (OR 1.49, 95%CI: 1.10, 2.02, P = 0.02) and having had gastroenteritis or having taken antibiotics during the 30 days prior to hospitalization (OR 11.55, 95%CI: 3.23, 41.23, P < 0.001; 3.09, 95%CI: 1.17, 8.12, P = 0.009, respectively) were significantly associated with intussusception. On the other hand, exclusive breastfeeding for at least two months was a protective factor (OR 0.48, 95%CI: 0.23, 0.99, P = 0.009). Anti-rotavirus vaccination did not correlate with risk of intussusception (OR 0.96, 95% CI: 0.41, 2.25, P = 0.92). Conclusions: These findings increase the awareness of intussusception among clinical and public health service providers to obtain a better susceptibility profile. Moreover, identifying children at higher risk of intussusception could be useful in vaccination counselling to intercept early symptoms and to reduce the number of serious cases.